Communication and diplomacy: The Arctic Council's communication of science on social media - Christensen, Miyase (Zenodo, 2022)
This case study appears in: Mays C, Laborie L, Griset P (eds) (2022) Inventing a shared science diplomacy for Europe: Interdisciplinary case studies to think with history . Techno-deterministic and techno-romantic understandings of the role of companies such as Facebook and Twitter have ascribed to these platforms powerful transformative roles in processes of social change. Recent research, however, has emphasized the need to analyze their influence within broader social, economic and political contexts. It is necessary to consider the platforms’ place within broader media ecologies, the actual levels to which users employ the platforms to bypass established media outlets (disintermediation), and whether mere presence online translates into use and impact. With these issues in mind, we examine the Arctic Council’s (social) media use in the service of science communication, its benefits and limitations, and the place of social media in the broader science diplomacy media ecology. You are consulting the updated and definitive version of this short publication. The latest version can always be accessed through: doi.org/10.5281/zenodo.6600877